Prevalence of fatty liver disease in children with obesity- a diagnostic study based on its ultrasound appearance - S., Ajitha J.; S., Bindu G.; Sadhakkathulla, K. Mohamed; G., Unnikrishnan (International Journal of Research in Medical Sciences, 2022)
Background: Non-alcoholic fatty liver disease is an asymptomatic involvement of the liver, can progress to chronic liver disease and must be identified at an early stage for good prognosis. The implementation of the appropriate therapeutic interventions is determinant of the attempts to treat it. For that purpose, early diagnosis and staging of the disease is essential. It seems that diagnostic imaging should be a first-line tool for the staging and monitoring pediatric NAFLD/NASH for appropriate interventions to be implanted in a timely way. This study evaluated the prevalence of fatty liver in relation with body mass index (BMI) by means of ultrasound in children of age group 6-15 years. Methods: In this cross-sectional study, 83 children aged 6 to 15 years, were selected randomly. The participants were examined by a pediatrician. Liver ultrasound was performed for all children and grade of fatty liver was determined. Results: There was a significant correlation between grade of fatty liver with BMI, our study showed a strong association between BMI and prevalence of fatty liver on ultrasound. Conclusions: According to the study hypothesis, based on BMI, the degree of NAFLD in children were predictable. Ultrasound of liver in grading of fatty liver is one of the assessments methods of fatty liver but it is not a diagnostic method; it is useful for prevention to reduce BMI.